Meningkatkan Hasil Belajar melalui Model Pembelajaran Problem Based Learning pada Muatan IPA Perkembangbiakan Tumbuhan pada Siswa Kelas VI - Sukowati, Indah (Universitas Negeri Malang, 2023)
Penelitian ini bertujuan mendeskripsikan peningkatan hasil belajar siswa dengan model pembelajaran Problem Based Learning (PBL) pelajaran IPA. Penelitian Tindakan Kelas (PTK) yang dilaksanakan adalah dua siklus, setiap siklus terdiri empat tahap yaitu perencanaan, pelaksanaan, observasi dan refleksi. Subyek penelitian siswa kelas VI A SDN Lowokwaru 3 berjumlah 28 siswa Indikator keberhasilan peningkatan hasil belajar siswa pada penelitian dilihat dari siswa tuntas KKM dengan nilai 75. Hasil penelitian menunjukkan terdapat peningkatan hasil belajar siswa ditunjukkan dari data tes yaitu nilai rata-rata siswa pada prasiklus sebesar 63,75, meningkat pada siklus I menjadi 80,30, dan pada siklus II nilai rata-rata siswa meningkat menjadi 86,60. Kata kunci: hasil belajar; PBL; perkembangbiakan tumbuhan Improving Learning Outcomes through the Problem Based Learning Model on Plant Breeding Science Content for the 6th Class Students This research aims to describe the improvement in student learning outcomes with the Problem Based Learning (PBL) model for science lessons. The Classroom Action Research (CAR) was carried out in two cycles, each cycle consists of four stages, namely planning, implementation, observation and reflection. The research subjects for class VI A students at SDN Lowokwaru 3 were 28 students. The indicator of success in increasing student learning outcomes in the research was seen from students who completed the KKM with a score of 75. The results of the research showed that there was an increase in student learning outcomes as indicated by test data, namely the average score of students in the pre-cycle was equal to 63.75, increased in first cycle to 80.30, and in second cycle the average student score increased to 86.60. Keywords: learning outcomes; PBL; plant reproduction